O ensino-aprendizagem de probabilidade em uma escola pública de Sorocaba/SP - Canaveze, Leila (Universidade Federal de São Carlos, 2013)
This qualitative work aims to describe and analyze a scenario of teachinglearning of the concept of Probability in three classes of the second grade of high school, a public school in the municipality of Sorocaba, State São Paulo. The look on this scenario of investigation was guided by the following research question: as occurs the teaching and learning in a context of tasks involving different probabilistic conceptions? For to answer this problem we developed a research field work where the researcher also played the role of teacher of such survey classes. With the help of the theory of semiotic representation records, analysis of the fieldwork revealed that the need to emphasize to students, through the application of tasks, the need for an adequate appropriation of terms pertinent to probabilistic language. The term that generated conflict in terms of meaning was the word luck. The option for minimizing the use of formulas has meant that students should use natural language and numerical registry as predominant forms of express written protocols of its activities. The use of products from records such as tree diagram and double-entry table had a supporting role in students ' writing process, getting restricted to set out the tasks explicitly demanded the student's activity using such forms of expression; or by the encouragement of a teacher-researcher. The educational intervention in support of the mobilization of different forms of semiotic registers, as the theoretical assumption of Raymond Duval, contributed to the learning of the concept of probability.
Keywords: Matemática; Tratamento da informação; Representação semiótica; Ensino médio; Probabilidade; Registros de representação semiótica; Probability; Information processing; Records of semiotic representation; High school; CIENCIAS EXATAS E DA TERRA::MATEMATICA